DAMPAK PENINGKATAN PANAS DAN JENIS REDUKTAN TERHADAP SAPROLIT: STUDI PENDAHULUAN - Bahfie, Fathan; Manaf, Azwar; Astuti, Widi; Nurjaman, Fajar; Prasetyo, Erik; Susanti, Diah; Sipahutar, Wahyu Solafide (Indonesian Mining Journal, 2024)
Indonesia significantly contributes to the global electric vehicle battery market due to its substantial medium- and low-grade nickel reserves. This study utilized saprolitic nickel ore from Halmahera, Maluku, Indonesia. However, the research on saprolite needs some improvements due to its complex mineral composition, which affected on the roasting process significantly. Therefore, a thorough understanding of the properties of laterite ores is critically important, particularly concerning laterite pre-reduction processes. The ore was finely sieved to a particle size of less than 100 mesh and then heated at temperatures of 250, 900, and 1150°C with the variation of reductant (anthracite and palm kernel charcoal). Extensive mineralogical analysis was conducted using X-ray diffraction (XRD), X-ray fluorescence (XRF), and scanning electron microscopy with energy-dispersive spectroscopy (SEM-EDS). The analysis of saprolite showed that it contains about 1.82% nickel, 30.47% iron, 10-20% magnesium, 4.86% aluminum, and 8.1% silicon by weight. Its mineral composition is mainly 53.1% goethite, 38.3% lizardite, and 8.7% quartz. The study found that goethite in saprolite was transformed into hematite around 250°C. At 900°C, the forsterite was crystallized, and at 1150°C, the ferronickel was formed. The transformation of lizardite is important as it affected on nickel diffusion within the iron matrix, which impacted on the material's properties. A thermal upgrading method with reductants like anthracite and palm kernel charcoal was used at lower temperatures to enhance the properties of saprolite. These findings provided valuable insights into saprolite's mineralogical composition and behavior, potentially offering improvements in various industrial processes and applications.